Persepsi Masyarakat terhadap Pemberian Bantuan Langsung Tunai di Masa Pandemi Covid-19: (Studi di Desa Air Asuk Kecamatan Siantan Tengah Kabupaten Kepulauan Anambas) - Husni, Alfi; Arfa, Desmayeti; Bagus Prastiyo, Endri; Rohana, Sita; Kesuma Putra, Iwan; Cahyo Wibowo, Tri; Aisyah, Siti (Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
The BLT policy launched by the government has drawn a lot of protests from the public, students and community leaders both nationally and regionally. The purpose of this study is to find out the Community's Perception of Providing Direct Cash Assistance (BLT-DANA DESA) during the Covid-19 pandemic in the people of Air Asuk Village, Kec. Central Siantan Kab. Anambas Islands. The research uses qualitative methods with community informants as beneficiaries of grants, and also people who do not receive grants. The research location is in the village of Air Asuk, Anambas Islands Regency. The results of the research are that people who tend to have negative perceptions are people who do not get help, that perception is based on internal and external perception factors, both what is felt, what is experienced while experiencing difficulties in the midst of an epidemic/pandemic, some are based on external factors, namely in the form of a stimulus when they know that the community is capable of getting help, and those who are affected have a negative perception because they have been influenced by other people around them who think that this is not right on target. Furthermore, there are also quite a lot of people who have a positive perception of the distribution of Covid-19 BLT-DD assistance, most of them have a positive perception, namely from the people who receive assistance, while the basis for their evaluation is that the distribution of aid funds is very useful and has been right on target, which tends to be based on internal factors. , as well as feelings of pleasure and help, and based on what is experienced.